Moisture dynamic sorption isotherms and thermodynamic properties of parchment specialty coffee (Coffea arabica L.) - Collazos Escobar, Gentil Andrés; Guzman, Nelson Gutierrez; Vaquiro Herrera, Henry Alexander; Amorocho Cruz, Claudia Milena (Coffee Science - ISSN 1984-3909, 2020)
Sorption isotherms represent an efficient and valuable tool for predicting the equilibrium moisture content of foods under different humidities and temperatures; thus, they are useful for determining shelf-life and safe storage conditions. The aims of this work were to determine the sorption isotherms of parchment specialty coffee at water activity values of 0.1−0.8 and temperatures of 25, 30, and 40 °C using the dynamic dew point method. The experimental sorption data were modeled using 12 different equations to represent the dependence of equilibrium moisture content on water activity and temperature. Thermodynamic properties were also obtained from the experimental data. The results showed a type II sigmoid shape according to Brunauer-Emmett-Teller (BET) classification, and the double log polynomial (DLP) equation successfully modeled the effects of temperature on the sorption isotherms, obtaining a good fit (R2adj = 0.99 and RMSE = 0.1 % dry basis). The dynamic dewpoint isotherm (DDI) method was advantageous for modelling due to its high availability of experimental data. Thermodynamic analyses showed that the net isosteric heat of sorption, Gibbs free energy, and sorption entropy decreased as equilibrium moisture content increased, and the compensation theory provided evidence that the sorption process was controlled by enthalpy (Tβ > Thm). Key words: Water activity; equilibrium moisture content; hygroscopicity; non-spontaneous; molecular ordering; compensation theory.